Universal Health Coverage for Inclusive and Sustainable Development : Country Summary Report for Brazil - Lindelow, Magnus (World Bank Group, Washington, DC, 2014)
Over the last 20 years, Brazil has seen profound economic, political, and demographic changes. After a period of military dictatorship (from 1964 to 1985), political and economic stability was achieved in the mid-1990s. The country has urbanized, improved access to water and sanitation, achieved solid economic growth, and reduced income inequality. It was one of the first Latin American countries to establish universal health coverage (UHC) as a fundamental right, based on the principles that health care is a duty of the state and should be free at the point of use. The reform in the late 1980s created the Unified Health System (Sistema Único de Saúde, or SUS) and was based on the principle that health care should be free at the point of use to all Brazilian citizens.